Method devised to improve technological reliability of machine parts - Кусий, Ярослав Маркіянович; Кук, Андрій Михайлович (Eastern-European Journal of Enterprise Technologies, 2015)
Considering reliability as a primary criterion in engineering machines and mechanical parts, we have analyzed why cylinder sleeves of drilling pumps fail in operation. Finishing and strengthening procedures in the technological process have proved to have essential influence on reliability indices. We have found that vibration technologies used in finishing and strengthening manufactured products can improve the operational qualities of machine parts. We have devised a method of centrifugal vibration strengthening to enhance reliability of the sleeves. The vibration machine for surround processing is adapted for centrifugal vibration strengthening of the shell. We have suggested a schematic diagram of equipment for centrifugal vibration strengthening as well as described the structure and operation principles of the equipment. The suggested industrial equipment is meant for centrifugal vibration strengthening of cylinder sleeves of drilling pumps. We have studied and analyzed profile charts of surfaces strengthened by vibration. The analysis of the research findings has revealed that the height and stepping parameters of the processed surface (Ra, Rz, Rр, Rmax, and S) have decreased 1.5–5.8 times, which proves that vibration strengthening has cut or deformed the protrusion tips on the surface relief. The act on the results of our field tests shows that after the centrifugal vibration strengthening of the cylinder sleeves of drilling pumps the average MTBF Тahas increased 1.79 times in comparison with original ground and heat treated sleeves. Besides, the economic effect is achieved through using steel of type 20 instead of type 70. We have specified research perspectives on optimizing the processing modes and developing practical recommendations on using centrifugal vibration strengtheners with a debalance drive aimed at improving the operational characteristics of sleeves as machine parts.